2015
DOI: 10.1016/j.vetpar.2015.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiology of human AE in Europe

Abstract: This review gives a critical update of the situation regarding alveolar echinococcosis (AE) in Europe in humans, based on existing publications and on findings of national and European surveillance systems. All sources point to an increase in human cases of AE in the "historic endemic areas" of Europe, namely Germany, Switzerland, Austria and France and to the emergence of human cases in countries where the disease had never been recognised until the end of the 20th century, especially in central-eastern and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 87 publications
2
70
0
9
Order By: Relevance
“…Intermediate hosts are small mammals, primarily rodents. A person can become infected by ingesting eggs occasionally, or by direct contact with dogs or cats and that can run around freely in nature and catch infection from the rodent [5], [6], [7].…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate hosts are small mammals, primarily rodents. A person can become infected by ingesting eggs occasionally, or by direct contact with dogs or cats and that can run around freely in nature and catch infection from the rodent [5], [6], [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the following decades, human AE cases were recorded in many more countries (Eckert, 1996;WHO, 2001a;Vuitton et al, 2003Vuitton et al, , 2015. Vuitton et al (2003) listed at least 28 countries with reported human AE cases, including two in North America, 13 in Eurasia and the Middle East, two in Asia, and 11 in (western and central) Europe.…”
Section: Human Cases Of Alveolar Echinococcosismentioning
confidence: 99%
“…To explain this situation, various factors have been proposed, including E. multilocularis dispersal by means of fox migrations in recent years, increase of fox populations, changes of landscape characters, and increased disease awareness, misdiagnosis and underreporting of human AE cases, and the use inadequate techniques for diagnosing E. multilocularis in foxes and other definitive hosts. An excellent overview of this discussion is presented in review articles of Vuitton et al (2003Vuitton et al ( , 2015.…”
Section: Expansion or New Detection Of Endemic Areas?mentioning
confidence: 99%
“…This is presumably because the domestic dog-livestock cycle associated with E. granulosus is relatively easier to interrupt (by worming dogs, preventing dogs from scavenging domestic animal remains at abattoirs and in the fields, and efforts at meat inspection), than the predominantly sylvatic E. multilocularis cycle (foxes-rodents). Not only is the prevalence of E. multilocularis apparently not decreasing, but the distribution of the parasite seems to be spreading in some areas of northern Europe and it seems to be emerging, becoming identified in some areas previously not considered particularly associated with the parasite, in other regions of the world (Conraths & Deplazes, 2015;Davidson, Romig, Jenkins, Tryland, & Robertson, 2012;Gottstein et al, 2015;Vuitton et al, 2015). For example, a case-finding study noted an increase in the prevalence of human AE in Switzerland over a 50-year period from 1956 to 2005, which could not be explained by improved diagnosis; the authors suggested that this change in prevalence may be associated with a rising fox population, which, in turn, is associated with a successful antirabies vaccination program (Schweiger et al, 2007).…”
Section: Specific Example Parasites: the Transition From Neglected Pomentioning
confidence: 99%